STUDENTS EXPERIENCE OF E-LEARNING, LEARNING PROCESS AND PERCEIVED LEARNING OUTCOMES IN ECONOMIC MATH COURSE - Yunia Mulyani Azis; Henny Suharyati; Sussy Susanti (UNIVERSITAS PAKUAN, 2019)
This paper reveals research findings about the effect of E-learning experiences on student learning outcomes felt for Mathematics Economics courses. This study examines perceived learning outcomes in terms of effectiveness, number and productivity of learning in the context of E-learning. The participants were undergraduate students at the School of Economis EKUITAS. The results are interpreted using quantitative and verification research approaches. The results show that the E-learning experience of students is significantly correlated with learning process, and have indirect effect on perceived learning outcomes. This study uses a learning model developed by Biggs and Moore. Specific recommendations for practitioners are also given, and their implications for educators are discussed. Finally, suggestions for further research on E-learning are provided.